DETEKSI MRSA (Methicillin Resistant Staphylococcus aureus) PADA PASIEN RUMAH SAKIT DENGAN METODE MALDI-TOF MS DAN MULTIPLEX PCR - Dian Wahyu Kemalaputri; Siti Nur Jannah; Anto Budiharjo (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2017)
Methicillin Resistant Staplylococcus aureus (MRSA) is a strain of Staphylococcus aureus which has been resistant to methicillin antibiotics and β-lactam group. The mechanism of MRSA resistance occurs because the Staphylococcus aureus produces Penicillin Binding Protein (PBP2a) encoded by the mecA gene that has low affinity to methicillin. Nowadays, MRSA is tested by resistance test using Oxacillin 1 ug. This method requires pure isolate and bacterial culture, so that the results can be seen in 5 days. To find a rapid and precise diagnostic technique for detecting MRSA, mecA gene detection utilizing PCR multiplex technique as the alternative diagnostics. This study aims to find a quick and precise alternative diagnostic technique for MRSA examination, which is utilizing MALDI-TOF MS and multiplex PCR technique.Keywords: MRSA, Staplylococcus aureus, MALDI-TOF MS, Multiplex PCR.